Perioperative Outcomes After Tracheostomy Placement Among Complex Pediatric Patients. (19th January 2021) - Davidson, Christian; Jacob, Benjamin; Brown, Ashley; Brooks, Rebecca; Bailey, Candace; Whitney, Cindy; Chorney, Stephen; Lenes‐Voit, Felicity; Johnson, Romaine F.
Abstract : Objectives/Hypothesis: To compare perioperative outcomes after pediatric tracheostomy placement based on patient complexity. Study Design: Retrospective case series. Methods: All patients that underwent tracheostomy placement at a tertiary children's hospital between 2015 and 2019 were followed. Children with a history of major cardiac surgery, sepsis, or total parental nutrition (TPN) were grouped as complex. Admission length, tracheostomy‐related complications, in‐hospital mortality, and 30‐day readmissions were recorded among complex and non‐complex patients. Results: A total of 238 children were included. Mean age at tracheostomy was 39.9 months (SD: 61.3), 51% were male and 51% were complex. Complex patients were younger at admission (29.9 vs. 46.8 months, P  = .03), more likely to have respiratory failure (81% vs. 53%, P  < .001) and more often required mechanical ventilation at discharge (86% vs. 67%, P  < .001). An additional 33 days after placement was required for complex children (95% CI: 14–51, P  = .001) and this group had more deaths (8% vs. 1%, P  = .02); however, both groups had similar complication and readmission rates ( P  > .05). Total charges were higher among complex patients ($700, 267 vs. $338, 937, P  < .001). Parametric survival analysis identified mechanical ventilation and patient complexity interacting to predict post‐tracheostomy admission length. Conclusions: Hospital discharge after pediatric tracheostomy was associated with patient complexity and further influenced by mechanical ventilation. Recognition that cardiac surgery, sepsis, or TPN can predict poorer perioperative outcomes can provide quality improvement strategies for these vulnerable children. Level of Evidence: 4 Laryngoscope, 131:E2469–E2474, 2021